The New Method of Sensor Data Privacy Protection for IoT - Yue Wu; Liangtu Song; Lei Liu (Shock and Vibration)
This article introduces the new method of sensor data privacy protection method for IoT. Asymmetric encryption is used to verify the identity of the gateway by the sensor. The IoT gateway node verifies the integrity and source of the data, then creates a block, and submits the block chain transaction. In order to avoid tracking the source of the data, a ring signature is used to anonymize the gateway transaction. The proxy re-encryption method realizes the sharing of encrypted data. On the basis of smart contracts, attribute-based data access control allows decentralized applications to finely control data access. Through experiments, the effects of sensor/gateway verification, transaction signatures, and sensor data encryption on performance are discussed. The results show that transaction delays are all controlled within a reasonable range. The system performance achieved by this method is also relatively stable.